FAKTOR KINERJA YANG MEMPENGARUHI PRODUKTIVITAS KARYAWAN PT GRAFIKA WANGI KALIMANTAN - Periyadi - (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2017)
Abstract,This study aims to determine whether there is influence of performance appraisal on employee productivity either partially or simultaneously.The method used in this study is quantitative research is a research model that requires the existence of the calculation of the numbers, while the approach used is a survey approach that is research that takes a sample of the population and use the questionnaire as a basic data collection tool.The results of this study indicate that, Quality, Quantity, Time, Cooperation, Loyalty significantly influenced and changes in the direction of employee productivity. This means that if the level of Quality, Quantity, Time, Cooperation, Loyalty perceived higher, then lead to higher productivity also Employees.